EFEKTIVITAS MEDIA AUDIO-VISUAL TERHADAP PENINGKATAN PENGETAHUAN DAN MOTIVASI IBU HAMIL UNTUK MENYUSUI - Aida Fitri; Mira Rizkia; Syifa Azzahra; Syahral Helfiva (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2023)
Exclusive breastfeeding is the ideal food for babies aged 0-6 months. But currently, globally exclusive breastfeeding is still low. This is due, among other things, to the lack of knowledge and motivation of mothers in giving exclusive breastfeeding Objective: to find out the effectiveness of exclusive breastfeeding audio-visual media toward the knowledge and motivation of pregnant women in breastfeeding in Banda Raya Community Health Center . Methods: The type of this research was pre-experimental study with one group pretest posttest. the 60 respondents were chosen by using total sampling. The data were collected by using questionnaires and analyzed by using Wilcoxon sign test Results: The result of the research showed that the exclusive breastfeeding audio-visual media towards th knowledge (p=0,000) and motivation (p=0,000) on the respondents. Conclusion: It was expected to the healthcare workers to hold more counselling related to exclusive breastfeeding to the the pregnant women by using audio-visual media in order to make them have more awareness, knowledge, and motivation related to breastfeeding.